Development and Psychometric Properties of MKDP Day’s Instrument as the Measurement of Personality Based on Worker in Kalimantan Selatan - M.Syarif Hidayatullah; Hayatun Thaibah (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2022)
The personality of a worker or employee is one of the important things to know. However, the development of personality measurement tools made directly in Indonesia is still relatively small. This study aims to develop and identify the psychometric properties of the MKDP Day's Instrument as a personality measurement tool in the context of the workforce in South Kalimantan. The research subjects were 1,123 people between the age of 20-30 years. MKDP Day's Instrument was made by researchers consisting of motivation, cooperation, discipline, and leadership dimensions by taking into account the personality theory of Needs from Murray and Papi Kostick from Kostick. The reliability test used a composite score with a stratified alpha coefficient. The validity test used was confirmatory factor analysis (CFA). The result of the reliability test is 0.832. The four dimensions of the instrument were able to explain 22% of the variables. It found 19 factors that can be formed on the instrument. There are 21 valid items from the initial 60 items with an uneven distribution between the dimensions. Further instrument development is needed to produce better psychometric properties.